The Dynamic and Fragile Nature of Eyewitness Memory Formation: Considering Stress and Attention - Wulff, Alia N.; Thomas, Ayanna K. (Frontiers in Psychology, 2021)
Eyewitnesses are often susceptible to recollection failures and memory distortions. These failures and distortions are influenced by several factors. The present review will discuss two such important factors, attention failures and stress. We argue that acute stress, often experienced by eyewitnesses and victims of crimes, directly influences attentional processes, which likely has downstream consequences for memory. Attentional failures may result in individuals missing something unusual or important in a complex visual field. Amongst eyewitnesses, this can lead to individuals missing details, even unusual or important central details, regarding the crime. Surprisingly, few studies have investigated attentional failures in eyewitness scenarios, and none have investigated the relationship between stress, attention, and witness memory. This review will discuss the impact of attentional failures, mainly those resulting from inattentional blindness, in applied contexts in order to bridge to eyewitness scenarios. In addition, we will integrate the applied literature on attentional failures with literature that examines the influences of arousal and stress on attention. We will conclude by presenting how future research may tease apart the independent contributions of arousal and stress on attentional failures and successes and how this research may inform understanding of eyewitness reliability.